The Influence of Innovative Behaviour and Proactive Personality on Employee Performance at the North Morowali Regency Fisheries Service - Lasmi; Andi Indriani Ibrahim; Niluh Putu Evvy Rossaanty; Nur Rizki Islianty (Universitas Muhammadiyah Palu, 2026)
This study aims to determine whether innovative behavior and proactive personality have a partial effect on the performance of employees at the North Morowali District Fisheries Office. This research employs a quantitative study with a descriptive-analytical approach, identifying independent variables (innovative behavior and proactive personality) and the dependent variable (employee performance). The sample for this study consisted of 67 individuals. The sampling technique used was saturated sampling, where all members of the population are included as samples if the population size is relatively small, less than 30 individuals. Saturated sampling is referred to as a census. The results of this study show that: 1) Based on hypothesis testing, it is known that the variables of Innovative Behavior (X1) and Proactive Personality (X2) have a significant partial effect on employee performance at the North Morowali District Fisheries Office. 2) Innovative Behavior has a positive and significant partial effect on employee performance at the North Morowali District Fisheries Office. 3) Employee Performance has a positive and significant partial effect on Innovative Behavior and Proactive Personality at the North Morowali District Fisheries Offi.